Prevalência e patogênese da infecção natural por Platynosomum fastosum (Digenea: Dicrocoeliidae) EM Felis catus (Linnaeus, 1758) do município de Maracanaú, Ceará - Braga, Roberta Rocha (2016)
Platynosomum fastosum (sin. P. illiciens, P. concinnum) is a digenean trematode of the family Dicrocoeliidae, that inhabits biliary tract of domestic and wild cats, whose infection goes from assymptomatic to letal. The prevalence of this trematode varies from 15 to 85% in tropical countries. In Brazil, available data is limited to case reports and few local epidemiological surveys. In Ceará, it was never performed an epidemiological survey, but a case report was recently published. The objective of this study was to calculate the prevalence of the P. fastosum infection, characterizing the main lesions associated to its pathogenesis, in free roaming cats in the municipality of Maracanaú, Ceará. It was performed an epidemiological pathological analitical cross-sectional survey about the P. fastosum infection in a sample of cats, received or captured by the Zoonosis Control Office of Maracanaú, between May/2014 and May/2015. This study was approved by the Animal Ethics Comitée of UFC (#40/2014). In a probabilist sample, 141 screened cats were euthanized by approved injection (CFMV, 2012) and submitted to necropsy. Livers and gallbladders were collected to recover trematodes and perform histopathology. Observed prevalence was 42,5% (60/141, IC95%=34,2 – 50,9). Fluke burden varied from 1 to 219. It was observed no difference in prevalence between males and females (p>0,05), but the adults were more frequently infected than the young ones (p<0,00001). Risk of cholangitis was at least three fold greater in infected ones (RP=3,23; IC95%=2,01-5,07; p<0,00001). Mononuclear infiltrates were the most frequent and significant findings, and the choledoco was the most affected site. Fibrosis, inflammation, glandular and mucosae hyperplasias were significantly different in choledocos of infected ones (p<0,01). Microscopic lesions considered precursors of cholangiocarcinoma were detected but no tumor was diagnosed. In summary, P. fastosum is present in the municipality of Maracanaú, Ceará, in moderated prevalence, in free roaming cats. Control propositions should be designed by multidisciplinar teams, evaluating sanitary and ecological aspects.